Remainder Theorem

Remainder theorem

Zeros of polynomials:

The value of a polynomial    p(x)

  at  x=a  is  obtained by putting  x=a  in p(x) and is denoted by  .

e.g.  Find the value of  p(x)=x^{2}-5x+6  at  x=-1.

Sol. On  putting  x=-1  in given polynomial , we get


This implies  p(-1)=12.

Thus value of p(x) at  x=-1  is 12.

 We say that a zero of a polynomial  p(x) is a number \large c such that p(c)=0.  It means \large c is  zero of  a polynomial  p(x)  if the value of that polynomial at \large c is  zero.

The zeros of polynomials is obtained by  equating  the given polynomial  p(x)=0.  We say p\left ( x \right )=0 is a polynomial equation and c is root of the polynomial equation p\left ( x \right )= 0.

Let  p\left ( x \right )=a be a constant polynomial, then p\left ( x \right )=ax^{0}.

Now replace x  with any number  we still get p\left ( x \right )=a. This implies constant polynomials has no zeros.  In case of zero polynomial , every real number is a zero of the zero polynomial.

Important observations:

(i) Every linear polynomial has one and only one zero.

Let     \large p(x)=ax+b, \, a\neq 0   be a linear polynomial,

then    p(x)=0  means   ax+b=0.

                                                \Rightarrow x=-\frac{b}{a}

So   x=-\frac{b}{a}    is the only zero of  p(x).

i.e.  a linear  linear polynomial has one and only one zero.

(ii) A zero of polynomial need not be 0.

e. g.  The zeros of     p(x)=x^{2}-4    are -2 and 2.

(iii) 0 may be a zero of polynomial.

e.g.  Take    p(x)=x(x-2)

(iv) A polynomial can have  more than one zero. 


Division algorithm in polynomials:

When we divide two numbers, we always get

Dividend =(divisor x quotient)+remainder,   where  0\leq remainder< divisor.  When remainder becomes zero, we say divisor and quotient both are factors of dividend.

Now, let two polynomials p(x)=3x^{4}-4x^{3}-3x-2  and g(x)=x-2 . Divide p(x) by g(x) 


{ Steps to divide a polynomial by a non-zero polynomial

  • First, arrange the polynomials (dividend and divisor) in the decreasing order of its degree
  • Divide the first term of the dividend by the first term of the divisor to produce the first term of the quotient
  • Multiply the divisor by the first term of the quotient and subtract this product from the dividend, to get the remainder.
  • This remainder is the dividend now and divisor will remain same
  • Again repeat from the first step, until the degree of the new dividend is less than the degree of the divisor.} 

Now        (x-2)(3x^{3}+2x^{2}+4x+5)+8= 3x^{4}+2x^{3}+4x^{2}+5x-6x^{3}-4x^{2}-8x-10+8

                                                              \, \, \, \, \, \, \, \, \, \, \, \, \, \, \, = 3x^{4}-4x^{3}-3x-2

                                                              \, \, \, \, \, \, \, \, \, \, \, \, \, \, \, \, \, \, =p(x)

 Hence  p(x)=g(x)\times q(x)+r(x)  where  deg(r(x))=0< 1=deg(g(x)).

In general , If p(x) and g(x) are two polynomials  such that deg(p(x))\geq deg(g(x))  and g(x)\neq 0, then we can find a polynomial q(x) as quotient  and r(x) as remainder, where r(x)=0  or deg(r(x))< deg(g(x)).

In the above example the divisior is a linear polynomial . In such a situation there is a way to find the  remainder called Remainder Theorem.

Remainder theorem

Let p(x) be any polynomial of degree greater than or equal to one  and let \large a be any real number. If  p(x) is divided by the  linear polynomial  x-a, then remainder is  p(a).

Proof. Let p(x) be any polynomial of degree greater than or equal to 1. Suppose p(x) is divided by (x-a) then by using division algorithm theorem , p(x) can be written as

\, \, \, \, \, \, \, \, \, \, \, \, \, \, p(x)=(x-a)q(x)+r(x)

since degree of r(x)< degree of q(x),  this implies degree of r(x)=0  ( \because degree of q(x)=1)

                                              \Rightarrow r(x)=c   (a constant polynomial)

                                            \Rightarrow p(x)=(x-a)q(x)+c

In particular if x=a  then  p(a)=c,  which proves the theorem. 

e.g. Find the remainder when x^{5}+x^{4}-2x^{3}+x^{2}+1 is divided by (x-1).

Sol. Here p(x)=x^{5}+x^{4}-2x^{3}+x^{2}+1 and zeros of x-1 is 1. 

so p(1)=(1)^{5}+(1)^{4}-2(1)^{3}+(1)^{2}+1



Hence by the remainder theorem , the remainder is 2.    

Also Read:         

Leave a Reply

Your email address will not be published.

IBPS Clerk Exam Date 2022 Out SSC MTS Admit Card 2022 Government Exam Calendar July 2022 CBSE Class 11 Mathematics Revised Syllabus 2022-2023 UGC NET 2022 Exam Date